MAIN ORGANIZATIONAL FACTORS THAT GENERATE TURNOVER INTENTIONS: A SYSTEMATIC LITERATURE REVIEW - Bierhals Hartwig, Thábata; Mendes dos Santos, Thierry; Heidtmann Bemvenuti, Renata (Revista Gestão da Produção Operações e Sistemas, 2024)
Purpose: carry out a systematic review of the literature to understand the main organizational factors that generate turnover intentions in workers. Theoretical framework: turnover is directly and indirectly related to an organization's costs and obtaining/retaining talent. It represents the termination of an employee voluntarily or involuntarily, and it is important to know the organizational factors that influence this rate to propose alternatives that keep employees engaged and the company with low turnover rates. Methodology/Approach: the method consisted of a systematic review of the literature. The Methodio Ordinatio was applied to understand the causes that generate turnover intentions among employees. Findings: the results made it possible to identify three main factors that generate turnover intentions, namely the lack of empowerment of leaders, lack of support for carrying out tasks and the intention in young professionals. Other factors were also observed, such as lack of emotional commitment, recognition, perspective, diversity in the organization, training, support from colleagues, inclusion in decision-making and identification with the company. Furthermore, precarious and unsafe environments, stress, the desire to open your own business, extroversion, a job market with good opportunities and unclear feedback also cause turnover intentions. Research, pratical & social implications: the study helps companies to efficiently invest their resources in the main causes of turnover so that they retain and attract talent. Originality/ Value: The value of the study refers to the potential for new research, focusing on specific areas. Furthermore, promising research would be the application of a survey in order to understand the factors that generate turnover intentions in specific companies.